Usage-inspired L2 instruction : researched pedagogy - Tyler, Andrea; Ortega, Lourdes; Uno, Mariko (Language learning and language teaching, 2018)
"This book presents a set of compelling essays collectively making a persuasive case for why a usage-based perspective on language is fast becoming a leading theoretical framework for investigating second language (L2) learning and the foundation for effective, innovative, engaging pedagogy. Drawing on 20 years of research in psychology, psycholinguistics, cognitive science, and linguistic theory, including discourse analytic approaches, the combined contributions paint a picture of theoretically-informed L2 pedagogy which emphasizes all facets of language as meaningful, embodied, and socially situated. The introduction and conclusion offer an outline of five foundational tenets essential to a usage-inspired pedagogy and a heuristic for developing usage-inspired L2 research and pedagogy. Each essay provides a unique vantage on usage-inspired L2 instruction and a demonstration of the efficacy of usage-based pedagogy. This volume will be invaluable for SLA researchers, graduate students, and classroom teachers interested in exploring usage-inspired L2 pedagogy"--